Ripple Effects of the Communities Preventing Childhood Obesity Project. Issue 2 (March 2020) - Gold, Abby L.; Bennett, Keith; Jansen, Rick J.; Mobley, Amy R.; Procter, Sandra B.; Smathers, Carol; Contreras, Dawn; Peters, Paula; Keim, Ann; Oscarson, Renee
This research examines the practice of community coaching within coalitions in the Communities Preventing Childhood Obesity project. A quasi-experimental design was used in seven Midwestern states. Each state selected two rural, low-income communities with functioning health coalitions. Coalitions were randomly assigned to be intervention or comparison communities. After 4 years of the coaching intervention, ripple effect mapping served as one method for examining the coalitions' work that may affect children's weight status. A research team from each state conducted ripple effect mapping with their two coalitions, resulting in 14 ripple maps. Community capitals framework and the social–ecological model were used for coding the items identified within the ripple maps. A quantitative scoring analysis determined if differences existed between the intervention and comparison coalitions in terms of the activities, programs, funding, and partnerships for social–ecological model score (e.g., individual, community, policy levels), community capitals score, and ripples score (e.g., number of branches formed within the maps). All scores were higher in intervention communities; however, the differences were not statistically significant ( p > .05). Assessing community assets, such as availability of a community coach, is necessary in order to decide whether to deploy certain resources when designing health promotion strategies.